2014
DOI: 10.1002/ceat.201300713
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Marangoni Effect on Mass Transfer in Inclined Falling Films

Abstract: Patchy particles are fabricated using a method of embedding‐into and extracting‐from thick, biocompatible, gel‐like HA/PLL films. Control over the patchiness is achieved by adjusting the stiffness of films, which affects embedding and masking of particles. The stiffness is adjusted by the concentration of gold nanoparticles adsorbed onto the surface of the films.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 72 publications
(79 reference statements)
0
1
0
Order By: Relevance
“…This surface phenomenon, referred to as Marangoni effect, can influence the particle behavior [2][3][4] and the interphase mass transfer rate [5][6][7], attracting attention of researchers on the onset and evolution of such solute-induced effect. Amounts of theoretical and experimental studies have demonstrated that the Marangoni phenomena are affected by many parameters, such as the mass transfer direction, initial solute concentration, and physical properties of the system [8][9][10] and also relate with surface-active agents [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…This surface phenomenon, referred to as Marangoni effect, can influence the particle behavior [2][3][4] and the interphase mass transfer rate [5][6][7], attracting attention of researchers on the onset and evolution of such solute-induced effect. Amounts of theoretical and experimental studies have demonstrated that the Marangoni phenomena are affected by many parameters, such as the mass transfer direction, initial solute concentration, and physical properties of the system [8][9][10] and also relate with surface-active agents [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%